Analysis of the virus propagation profile of 14 dengue virus isolates in Aedes albopictus C6/36 cells - Atitaya Hitakarun (BMC Research Notes, 2020)
Abstract Objective The mosquito transmitted RNA virus dengue virus (DENV) shows significant variation as a consequence of the lack of proofreading activity of the RNA-dependent RNA polymerase that synthesizes new virus genomes. How this variation affects DENV replication, and how this in turn impacts drug development remains largely unknown. Given the technical limitations in working with large numbers of isolates few studies have sought to investigate this area. This study used a panel of 14 DENV isolates of different serotypes and origins to determine how much virus replication in Aedes albopictus C6/36 cells was affected by DENV variability. Results The results showed that there was considerable variation, with peak titers ranging from 6Log10 to 8Log10, and maximum titer being reached from day 3 to day 9 post infection. While strains from DENV 1 and 4 serotypes showed considerable uniformity, DENV 2 and 3 strains showed much greater variation. Overall, these results show that serotype specific strain variation can have a significant impact on DENV replication, suggesting that studies either investigating DENV pathogenesis or developing drug therapeutics should consider the contribution of DENV variability.